Is Radiographic Control Necessary after Every Lengthening of Magnetically Controlled Growing Rod?. Issue 1 (April 2016) - Yilgor, Caglar; Alanay, Ahmet
Introduction: A well-accepted imaging follow-up protocol to confirm the amount of lengthening, and check for the curve and the status of the implants for MCGR is not yet established. AP-lateral XR after each lengthening (usually every 2–3 months) is suggested. The aim of this study was to find out whether radiation exposure after every lengthening can be justified or not. Material and Methods: A retrospective analysis of 14 consecutive patients (12F, 2M) with EOS of different etiologies treated by MCGR. Mean age was 7 (3–10). Examination of the back in terms of implant prominence was done carefully after each lengthening. Lengthening interval was 2–3 months. Patients had pre- and post-lengthening AP-lateral XR in every visit in the beginning of experience and this was subsequently changed to only AP post-lengthening XR. The XR were analyzed for the presence of failure to lengthen, collapse between 2 procedures and incidental mechanical failures such as rod breakages, hook/screw pullout. Results: Mean preop coronal Cobb of 69.6° (38–101) was corrected to 39.1° (16–76) at the final follow-up. Average followup was 24 months (6–52). A total of 101 lengthenings were performed. 173 pre- and post-lengthening XR (110 AP, 63 lateral) were taken. There were a total of 5 mechanical failures in 2 pts. 4 were rod or substance breakages and 1 was hook dislodgement. All 5 were diagnosed in a non-planned control with the patient applying for either prominence of implants and/or history of trauma or unremitting pain. No other incidental mechanical failures were noted in any routine XR. Conclusion: Routine XR taken before and after each lengthening procedure of a MCGR is not likely to reveal any significant findings. Post-lengthening AP XR with a decreased frequency (every 6 months) and AP-lateral XR only after a significant complaint or clinical findings should be considered.